Hall effect on MHD transient flow past an impulsively started infinite horizontal porous plate in a rotating system - Prabhakar Reddy, Bijjula (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the effect of Hall current on an unsteady MHD transient three dimensional flow of an electrically conducting viscous incompressible fluid past an impulsively started infinite horizontal porous plate relative to a rotating system has been studied. It is assumed that the entire system rotates with a constant angular velocity about the normal to the plate and a uniform magnetic field is applied along the normal to the plate and directed into the fluid region.
Keywords: Hall currents; MHD; transient; rotation; horizontal plate; Galerkin FEM